Australia : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper on Australia discusses prospects and ramifications of China's economic transition. Australia and China have strong linkages that are growing over time as China carries on with its economic transition. Trade in commodities and services are constantly growing. Australia has established itself as a dominant player in some key Chinese import needs, particularly for steel. The stylized facts also demonstrate that the rest of Asia is increasingly important for Australia. The charts for tourism, education, and the destination of exports illustrate that both advanced and emerging Asia already have a growing impact. The paper shows that the rest of Asia's trade linkages with Australia are similar in size to the linkages between Australia and China. China may be Australia's largest trading partner, but the rest of Asia is also a rapidly growing region, with potential markets for Australian expansion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet